Peningkatan Kemampuan Pemecahan Masalah Matematika Mahasiswa Melalui Pemanfaatan GUI MATLAB untuk Sistem Persamaan Non-Linier - Syaharuddin, Syaharuddin; Negara, Habibi Ratu Perwira; Sucipto, Lalu; Mandailina, Vera; Abdillah, Abdillah (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2026)
Learning nonlinear equation systems requires the integration of conceptual understanding and computational skills, which in practice remains a challenge for students due to the abstract nature of the material. This community service activity aims to improve students' understanding of nonlinear equation systems through the use of MATLAB Numeric GUI as an interactive learning medium. There were 23 students from the Mathematics Education Study Program at UIN Mataram participating in this activity. The implementation methods included concept socialization, GUI usage demonstrations, case-based independent practice, and direct mentoring. The evaluation system used three essay questions to measure mastery of concepts, numerical procedures, and MATLAB GUI usage skills. The evaluation results show that the average achievement of students is 70, with a maximum score of 80 and a minimum score of 60. The average score for the first question reached 68.67, increased to 69.33 for the second question, and increased again to 72.67 for the third question, showing a trend of increasing understanding by 4 points from the initial question to the final question. These findings indicate that the use of the MATLAB Numeric GUI can strengthen conceptual understanding, improve computational skills, and help visualize numerical processes more concretely in learning nonlinear equation systems.